Protective and pathologic immune responses in human tegumentary leishmaniasis - Carvalho, Edgar M.; Carvalho, Lucas P.; Passos, Sara; Schriefer, Albert (Frontiers in Immunology, 2012)
Studies in the recent years have advanced the knowledge of how host and parasite factors contribute to the pathogenesis of human tegumentary leishmaniasis. Polymorphism within populations of Leishmania from the same species have has been documented, ; indicating that infection with different strains may lead to distinct clinical pictures and can also interfere in the response to treatment. Moreover, the detection of parasite genetic tags for the precise identification of strains will improve the diagnostics and therapy against leishmaniasis. On the host side, while a predominant Th1 type immune response is important to control parasite growth, it does not eradicate Leishmania and, in some cases, does not prevent parasite dissemination. Evidence have been has accumulated showing the participation of CD4+ and CD8+ T cells, as well as macrophages, in the pathology associated with L. braziliensis, L. guayanensis and L. major infection. The discovery that a large percentage of individuals that are infected with Leishmania do not develop disease will help to understand how the host controls Leishmania infection. As these individuals have a weaker type 1 immune response than patients with cutaneous leishmaniasis, it is possible that control of parasite replication in these individuals is dependent, predominantly, on innate immunity, and studies addressing the ability of neutrophils, macrophages and NK cells to kill Leishmania should be emphasized.